Дослідження в музеях закладів системи вищої освіти: українські реалії та європейський контекст - Муравська, Світлана; Muravska, Svitlana (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті здійснено спробу проаналізувати особливості реалізації дослідницького завдання музеями закладів вищої освіти. На тлі порівняння із ситуацією за кордоном доведено, що аксіоматичне твердження про першо-черговість такого завдання є помилковим. Organization and conducting of research is one of the main tasks for the museum in accordance with the International Council of Museums definition. This function has often determined the general meaning of such "temples of muses" existence, the principles of their fund-formation, the specifics of work with students, and other moments. However, the big changes in the museum activities of museums have happened in the XXI century Based on the analysis of empirical material gathered in museums and collections of 74 HEE on Western Ukraine during 2013–2017, the author argues the axiomatic assertion about the priority of such a task is erroneous one and less than 20 % of them museums continue to be engaged in the research work. Comparison with the situation abroad shows that the causes and trends are similar ones.
Research in Museums of Higher Educational Establishments: Ukrainian Realities and European Context
Keywords: музей; колекція; заклад вищої освіти; дослідження; museum; collection; institution of higher education; research